α-synuclein decreases the abundance of proteasome subunits and alters ubiquitin conjugates in yeast - Popova, Blagovesta; Galka, Dajana; Häffner, Nicola; Wang, Dan; Schmitt, Kerstin; Valerius, Oliver; Knop, Michael; Braus, Gerhard H. (Cells, 2021)
Parkinson’s disease (PD) is the most prevalent movement disorder characterized with loss of dopaminergic neurons in the brain. One of the pathological hallmarks of the disease is accumulation of aggregated α-synuclein (αSyn) in cytoplasmic Lewy body inclusions that indicates significant dysfunction of protein homeostasis in PD. Accumulation is accompanied with highly elevated S129 phosphorylation, suggesting that this posttranslational modification is linked to pathogenicity and altered αSyn inclusion dynamics. To address the role of S129 phosphorylation on protein dynamics further we investigated the wild type and S129A variants using yeast and a tandem fluorescent timer protein reporter approach to monitor protein turnover and stability. Overexpression of both variants leads to inhibited yeast growth. Soluble S129A is more stable and additional Y133F substitution permits αSyn degradation in a phosphorylation-independent manner. Quantitative cellular proteomics revealed significant αSyn-dependent disturbances of the cellular protein homeostasis, which are increased upon S129 phosphorylation. Disturbances are characterized by decreased abundance of the ubiquitin-dependent protein degradation machinery. Biotin proximity labelling revealed that αSyn interacts with the Rpt2 base subunit. Proteasome subunit depletion by reducing the expression of the corresponding genes enhances αSyn toxicity. Our studies demonstrate that turnover of αSyn and depletion of the proteasome pool correlate in a complex relationship between altered proteasome composition and increased αSyn toxicity.
Gesehen am 04.11.2021